2018 Kidney Disease: Improving Global Outcomes (KDIGO) Hepatitis C in Chronic Kidney Disease Guideline Implementation: Asia Summit Conference Report - Li, P.K.-T. (Elsevier Inc, 2021)
10.1016/j.ekir.2020.05.001